충남 서산에서 가을철에 관측한 초미세먼지의 광흡수 특성 - 박승식(Seungshik Park); 이광열(Kwangyul Lee); 이민도(Mindo Lee) (한국대기환경학회지(국문), 2020)
In this study, a real-time monitoring of aerosol light absorption was conducted using a dual-spot sevenwavelength aethalometer with a PM2.5 impactor between October 18 and November 05, 2019 at Chungcheong region air quality research center in Seosan, Chungcheongnam-do. Over the study period, light absorption coefficients of atmospheric aerosol and brown carbon (BrC) at wavelength of 370 nm peaked in both the morning (07:00~09:00 LT) and evening hours (17:00~24:00 LT), but with more predominance of their absorption coefficients during nighttime hours. This could possibly be due to light-absorbing organic aerosols from biomass burning emissions at night around the sampling site. Contribution of black carbon (BC) and BrC absorption to total aerosol light absorption at 370 nm wavelength was 70.4 and 29.6% at 08:00 LT and 53.5 and 46.4% at 18:00 LT, respectively. For the time when the contribution of BC absorption (~33%) to total aerosol absorption at 370 nm was approximately two-fold lower than BrC absorption contribution (~67%), absorption Ångström exponent (AAE) values of aerosol particles in the 370~520 nm wavelength range (AAE370-520) were greater than 2.0, reaching maximum of 3.1. On the other hand, when BC absorption accounted for most of the total aerosol absorption, aerosol AAE370-520 values were close to 1.0. For the periods when light absorption by aerosol particles significantly increased, AAE370-660 of BrC estimated between the wavelengths of 370 and 660 nm was in the range of 3.4~5.1. The difference in AAE values among the excursion periods was likely due to the considerable difference in water-soluble and insoluble BrC absorption. Furthermore, correlation analyses among water-soluble organic carbon (OC), total OC concentrations, and BrC absorption coefficients at 370 nm wavelength suggest that light absorption by BrC particles was clearly influenced by not only water-soluble OC fractions, but water-insoluble OC fractions. KCI Citation Count: 0